ANALISIS RASIO KEUANGAN DAN ALTMAN Z-SCORE UNTUK MENILAI KINERJA KEUANGAN SERTA MEMPREDIKSI KEBANGKRUTAN PADA PT. TANDES LAUTAN PERIODE 2016-2019 - Yoga, Dwi Yoga Imam Baskoro; Kusuma, Indra Cahya; Setiawan, Ade Budi (Jurnal Akuntansi Kompetif, 2024)
This study was conducted to analyze financial ratios and altman z-score to assess financial performance and predict bankruptcy at PT. Tandes Lautan in 2016-2019. This study uses a quantitative descriptive method by calculating and analyzing liquidity ratios, solvency ratios, profitability ratios and activity ratios as well as analyzing bankruptcy with the Altman z-score method. The results of the analysis show that (1) the liquidity ratio in 2016-2019 is assessed from the current ratio, quick ratio and cash ratio is not good (2) the solvency ratio in 2016-2019 is assessed from the debt to asset ratio, debt to equity ratio, long term debt to equity ratio is not good (3) the profitability ratio in 2016-2019 is assessed from the gross profit margin in good condition, assessed from the operating profit margin, net profit margin, return on assets, return on equity is not good (4) activity ratio in 2016 -2019 is judged from poor receivable turn over, inventory turn over, working capital turn over, fixed assets turn over in good condition, and total assets turn over not good (5) Z Score calculation from 2016-2019 the value is below 1, 1 which is called the bankruptcy value.